PENGARUH PEMBELAJARAN KOOPERATIF TIPE TAI BERBASIS CHEMOENTREPRENEURSHIP TERHADAP MOTIVASI BERWIRAUSAHA DAN PENGUASAAN KONSEP SISWA PADAMATERI KOLOID - Marwah Marwah; Citra Ayu Dewi; Ratna Azizah Mashami (Universitas Pendidikan Mandalika Mataram, 2016)
The influence of cooperative learning type TAI based on chemoentrepreneurship to entrepreneurship motivation and conceptual understanding of students on colloidal system concept. Colloidal system concept was a concept that requires highly analysis with mastery of concepts that must be understood and require students practice in daily life. Learning will be more meaningful and provide a deep understanding of the learners when learning adapted to the characteristics of the subject matter. One effective solution was implement the cooperative learning type TAI based on chemoentrepreneurship. This study aimed to determine the influence of cooperative learning type TAI based on chemoentrepreneurship to entrepreneurship motivation and conceptual understanding of students. The study design used was pretest-posttest control group design, the sampling technique used cluster random sampling. The population in this study were all students of grade XII IPA SMA AL-Hamzar, Thatwas 50 students were divided into an experimental group of 26 students and a control group of 24 students. Entrepreneurship motivation analysis technique using multivariate test obtained scores of experimental group 63%, 74% and score of control group 66%, 68%. While conceptual understanding data using multivariate test with SPSS 16.0 for windows which scores obtained from initial test and final test on the conceptual understanding was no difference between the experimental group and control group that why used T test. Results obtained there was significant influences of cooperative learning type TAI based on chemoentrepreneurship to entrepreneurship motivation and it had no influence on students' conceptual understanding with sig = 0.304 > 0.05. So it can be concluded that there was no influence of cooperative learning type TAI based on chemoentrepreneurship to conceptual understanding of students.